2020
DOI: 10.1155/2020/8839761
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation on the Energy Storage Characteristics of Red Sandstone in Triaxial Compression Tests with Constant Confining Pressure

Abstract: The elastic energy stored in deep rock in three-dimensional stress environment is the energy source of rockburst. To investigate the energy storage characteristics of deep rock under different confining pressures, a series of triaxial single-cyclic loading-unloading compression tests were conducted on red sandstone specimens under eight confining pressures. The input energy density, elastic energy density, and dissipative energy density of the specimen in axial, circumferential, and total directions can be obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
(58 reference statements)
0
3
0
Order By: Relevance
“…It has been reported that a certain miscalculation often happens during rockburst proneness discrimination using these indexes [142]. Recently, Gong et al [143][144][145] first discovered the linear energy storage law, which was proved to be applicable to many materials such as rock, coal [146], and concrete [147] and various test types (the uniaxial compression test [148][149][150][151][152], triaxial compression test [153,154], tension test [144], shear test [155], and three-point flexural loading test [156]). They also established a new rockburst proneness criterion based on the residual elastic energy index, and the accuracy of rockburst discrimination was greatly improved.…”
Section: Investigating the Mechanical Properties Of Tir In Complex En...mentioning
confidence: 99%
“…It has been reported that a certain miscalculation often happens during rockburst proneness discrimination using these indexes [142]. Recently, Gong et al [143][144][145] first discovered the linear energy storage law, which was proved to be applicable to many materials such as rock, coal [146], and concrete [147] and various test types (the uniaxial compression test [148][149][150][151][152], triaxial compression test [153,154], tension test [144], shear test [155], and three-point flexural loading test [156]). They also established a new rockburst proneness criterion based on the residual elastic energy index, and the accuracy of rockburst discrimination was greatly improved.…”
Section: Investigating the Mechanical Properties Of Tir In Complex En...mentioning
confidence: 99%
“…With further exploration, it is found that the rocks possess the linear energy storage law in three-dimensional compression [59], preset angle shear test [60], and fracture test [61], as well as the pre-heated granite specimens in the UC test [46]. erefore, when investigating the failure of deep high-temperature rock, adopting the linear energy storage law can accurately calculate extremity energy storage as well as residual elastic strain energy during the whole process, to realize the quantitative evaluation of rockburst proneness.…”
Section: Development Trend Of Rockburst Test Considering the Temperature Effectmentioning
confidence: 99%
“…Before the failure of the rock mass, a large amount of elastic strain energy will accumulate in the stress concentration area. When the elastic strain energy is released suddenly in the free face, the rock will produce violent brittle failure in a short time, causing serious dynamic disasters [13][14][15]. Rock mass with rockburst proneness is usually elastic-perfectly brittle rock mass with few cracks or only hidden cracks [4,16,17].…”
Section: Introductionmentioning
confidence: 99%